Angular acceleration estimation-based incremental nonlinear dynamic inversion for robust flight control. (December 2021) - Li, Yu; Liu, Xiaoxiong; Lu, Peng; He, Qizhi; Ming, Ruichen; Zhang, Weiguo
Abstract: The robustness of the incremental nonlinear dynamic inversion (INDI) technique depends on the accuracy of the feedback angular accelerations. However, angular accelerations are usually not readily available. They are obtained from differentiation and are sensitive to time delays and noise. These undesired effects decrease the robustness of the system to disturbances and model uncertainties. A novel INDI-based flight control strategy, named angular acceleration estimation-based INDI (EINDI), is proposed in this paper to solve the problem of acquiring accurate angular accelerations. The EINDI method combines the control surface deflections and an adaptive technique to estimate angular accelerations, which can reduce the effects of noise and time delays on angular accelerations, thereby ensuring the robustness of the system. Furthermore, stability analysis based on the Lyapunov theory demonstrated that the EINDI was robust to model uncertainties. Simulation results showed that EINDI was effective in reducing the influence of noise and time delays and overcoming the influence of the center of gravity (CG) changes and a series of model uncertainties. Highlights: The angular rate dynamics equation for aircraft with a center of gravity (CG) change. Angular acceleration estimation technique based on existing information and adaptive algorithm. Projection operator-based adaptive law. Angular acceleration estimation-based Incremental nonlinear dynamic inversion (EINDI) control technology.